Sarana dan Prasarana dalam Menunjang Hasil Belajar Pendidikan Agama Kristen bagi Peserta Didik - Yessi Carolina; Merilyn; Defri Triadi (Harati: Jurnal Pendidikan Kristen, 2024)
This study aims to analyze the infrastructure that supports student learning outcomes in Christian Religious Education lessons at SMAN 1 Palangka Raya. The research method is qualitative with descriptive research type. Data collection techniques with interviews, observation, and documentation. The results of the research of existing infrastructure facilities at SMAN 1 Palangka Raya are in good condition, but still do not meet the standards in accordance with the Regulation of the Minister of National Education Number 24 of 2007 Standards for facilities and infrastructure of SMA / MA General Education. In this case there are some that still need to be completed and considered such as religious study rooms whose facilities such as air conditioning and LCD that need to be repaired or replaced, as well as a place of worship that needs to be provided specifically for students who are Christian. The completeness of the existing infrastructure at SMAN 1 Palangka Raya can meet the needs of students and teachers, so that in the process of teaching and learning activities can run effectively and efficiently, and the learning outcomes obtained by students XI MIPA 2 through the learning process are supported by educators and infrastructure.